Pengaruh Dukungan Sosial Suami Terhadap Kepuasan Pernikahan Istri pada Pasangan Dewasa Awal di Jawa Barat Tahun 2025 - M Ridho Akbar Aq; Grin Rayi Prihandini (Publikasi Indonesia, 2026)
This study aims to examine the influence of husband's social support on wife's marital satisfaction among early adult couples in West Java. The phenomenon of high divorce rates, particularly within the first five years of marriage, provides the background for the importance of conducting this research. The research method employed a non-experimental quantitative approach with a causal-comparative design. Research participants involved 138 wives aged 20-40 years who had been married for less than five years and resided in West Java. Data collection utilized two instruments: the Marital Satisfaction Scale based on the ENRICH model with 36 statement items and the Social Support Scale based on Sarafino's theory with 24 statement items. Data analysis techniques employed simple linear regression to test the research hypothesis. Analysis results indicated that husband's social support significantly influenced wife's marital satisfaction with an F value of 39.550 and a significance level of 0.000. The correlation coefficient showed a value of 0.475 with a coefficient of determination of 22.5 percent, indicating that husband's social support could explain a quarter of the variation in wife's marital satisfaction. Social support encompassing emotional, appraisal, instrumental, and informational dimensions proved to be a protective factor that strengthened the quality of marital relationships. This research provides practical contributions to the development of marital counseling intervention programs and strengthens the theoretical foundation regarding the importance of social support in the context of intimate relationships among early adult couples.